The Impact of Postmortem Interval on the Reliability of Forensic Autopsy Evidence in Murder Cases: A Comprehensive Analysis in Nairobi, Kenya - Stephen Kase; Jenne Batdorff (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: Postmortem interval (PMI) significantly impacts the accuracy and interpretation of forensic autopsy evidence, especially in murder cases. In Nairobi, Kenya, where resources and infrastructure may be limited, understanding the relationship between PMI and evidence reliability is crucial for effective investigations and prosecutions. Methods: A retrospective analysis was conducted on 150 murder cases in Nairobi between 2018 and 2023. Cases were stratified based on PMI (early PMI <24 hours, intermediate PMI 24-72 hours, late PMI >72 hours). Autopsy reports were reviewed to assess the reliability of evidence related to the cause of death, manner of death, and identification. Statistical analyses were performed to examine the correlation between PMI and evidence reliability. Results: As PMI increased, the reliability of certain forensic evidence decreased significantly. Early PMI cases showed the highest reliability for determining the cause of death, manner of death, and identification. In contrast, late PMI cases often presented challenges in interpreting evidence due to decomposition, scavenging, and environmental factors. This led to uncertainties in determining the cause and manner of death, particularly in cases involving blunt force trauma or asphyxia. Conclusion: This study highlights the critical impact of PMI on the reliability of forensic autopsy evidence in murder cases in Nairobi. Early PMI examinations are essential for obtaining accurate and reliable evidence, especially in resource-limited settings. Standardized protocols, improved infrastructure, and ongoing training for forensic pathologists are crucial to mitigate the challenges associated with PMI and ensure justice in murder investigations.